Perceptions and analysis of digital risks - Capelle, Camille; Liquete, Vincent (Wiley-ISTE, 2022)
The concept of digital risk, which has become ubiquitous in the media, sustains a number of myths and beliefs about the digital world. This book explores the opposite view of these ideologies by focusing on digital risks as perceived by actors in their respective contexts. Perceptions and Analysis of Digital Risks identifies the different types of risks that concern actors and actually impact their daily lives, within education or various socio-professional environments. It provides an analysis of the strategies used by the latter to deal with these risks as they conduct their activities; thus making it possible to characterize the digital cultures and, more broadly, the informational cultures at work. This book offers many avenues for action in terms of educating the younger generations, training teachers and leaders, and mediating risks.
Keywords: Digital media -- Social aspects; Computer security; Risk; Sécurité informatique; Risque; Digital media; Social aspects